The relationship between emotional intelligence and writing ability of Iranian EFL learners - Sadeghi, Karim; Farzizadeh, Bahareh (BELT - Brazilian English Language Teaching Journal, 2014)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 10pt; mso-ansi-language: EN-US; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: SimSun; mso-font-kerning: 1.0pt; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-no-proof: yes;">As opposed to traditionally attached advantage to IQ, Emotional Intelligence (EI) theory is increasingly characterized as contributing to students' ability to jump-start their achievement. In this study, the body of female BA sophomores of English Literatureat Urmia University, (N =47), was given a close look in terms of their EI, uaing an intact group sampling procedure. The starting point was the students' being given Bar-On's Emotional Quotient Inventory, for which the participants were asked to respond based on the relevance of the statements to themselves using a Likert Scale. Thereafter, the students' scores on the advanced writing coursefinal exam were obtained and correlated with their EI scores. The scoring of writing papers was done analytically following pre-specified criteria. The writings were scored once by two trained raters, yielding the inter-rater reliability of 0.8.Analyses conducted through Multiple Regression indicated a positive relationship between writing ability and emotional self-awareness, a subcategory of EI. This finding can create a room for highlighting emotions in one's educational life.